PENGARUH PENGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA BERDASARKAN DATA STATISTIK DI MA AL-MUSYAWIRIN - diya, khalimatus Sakdiya (Al Naqdu, 2024)
The education sector continues to develop rapidly, especially in terms of the use of technology to improve learning outcomes. Interactive learning is a promising educational innovation that combines technology with education to make the learning process more interesting and dynamic. In an era where technology and information are part of the daily lives of the younger generation, it is hoped that the use of interactive learning media will increase students' desire to learn. Students' enthusiasm for learning is an important component in their learning success. Interactive learning is one way to make learning more interesting and participating. The aim of this research is to find out how the use of interactive learning media impacts students' desire to study at MA Al-Musyawirin. Statistical data is analyzed systematically after being collected through quantitative methods. The research results show that the use of interactive learning tools increases the desire to learn.